Effects of Bifidobacterium longum longum 35624® on the Symptoms and Quality of Life in Patients with Irritable Bowel Syndrome: Results of the Multicenter Observational Program SAGA - V. T. Ivashkin; E. A. Poluektova; Z. A. Mamieva (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to evaluate the effects of the probiotic Symbiosys Alflorex (Bifidobacterium longum longum 35624®) on the symptoms and quality of life in patients with irritable bowel syndrome (IBS).Materials and methods. A multicenter, observational program (SAGA) was conducted to evaluate the effects of Symbiosys Alflorex on symptoms and quality of life in patients with IBS, which enrolled 3,116 patients and 246 physicians from 48 cities of Russia. Eligible patients were diagnosed with IBS according to the Rome IV Criteria and clinical guidelines of the Russian Association of Gastroenterology and the Association of Colorectal Surgeons of Russia. Patients received standard-of-care treatment and add-on therapy with Symbiosys Alflorex 1 capsule once daily for 28 days, followed by Symbiosys Alflorex alone for 2 months. The intensity of symptoms and severity of IBS were assessed using the 7 Symptoms in 7 Days (“7 × 7”) and the Irritable Bowel Syndrome Severity Scoring System (IBS-SSS) questionnaires, respectively. The Irritable Bowel Syndrome Quality of Life (IBS-QоL) questionnaire was used to assess the quality of life. Stool abnormalities were assessed using the Bristol Stool Scale.Results. After the course of standard-of-care treatment and add-on therapy with Symbiosys Alflorex, 25.8 % of patients achieved clinical remission. After 3 months of probiotic treatment, 76.9 % of patients achieved clinical remission. A significant decrease in the “7 × 7” score was observed, with the mean total score decreasing from 15.8 to 9.77 after the main treatment course and to 3.44 by the end of the study. Stool consistency became normal in 40.1 % of patients by the end of the first month and in 76.8 % after 3 months of follow-up. Changes in the IBS-QoL score showed a significant improvement in the quality of life.Conclusions. Add-on treatment with Symbiosys Alflorex 1 capsule once daily for 3 months helps to improve IBS symptoms and quality of life of patients. Symbiosys Alflorex has a favorable safety profile.